WORD FORMATION FOR TRANSLATORS - Engliana Engliana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2012)
Translators often encounter challenges in choosing the best meaning from source text into target text during translation process, in this case, transferring from English language into Indonesian language. One of the influential factors in word or phrase choice in such action is the translator’s understanding of the source language and text. Word formation atau ‘pembentukan kata’ is one of the knowledge the translators have to learn since translation definitely engages with meanings in words and phrases that are mostly related to word formation. This paper merely describes ten word formations in English language, which can be applied to Indonesian language, the translators need to know that will surely help them to have the right meaning and finally decide the best language choice in translating.Keywords : word formation, lexical items, suffix, prefix